Notice of the Ancient Church of St Helen at Aldcambus, and of Fragments of a Monastic Building at Luffness; with Plans (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article discusses the ruined remains of a church that has now been incorporated into another parish, covering the history of the church and some notes on its condition from the 1840s. There is also a short notice of some ruined church or monastic buildings near Aberlady.